Pelatihan Pembuatan Aromaterapi Berbasis Reed Diffuser sebagai Solusi dalam Manajemen Stress - Willi Wahyu Timur; Devi Mardiyanti; Indah Kurniawati; Naniek Widyaningrum (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Stress management plays an importantt role int dealing with the level of productivity of learning activities. Poor stress management can contribute to a lack of preparedness in facing global health crisis situations, decreased academic achievement, critical thinking skills and learning motivation. Stress arises due to an individual's inability to deal with burdens or pressure, especially those imposed by students within the scope of education. Aromatherapyk is used as an alternative to relax the body, emotions and stress. Through product creation and implementation of health education programs, training in making aromatherapy reed diffusers focuses on community empowerment by involving students and teaching staff. This service is carriedd out with the aimm of helping manage students' academic growth through psychoeducational activities about stress management, preventing and reducing stress symptoms and remaining productive in daily life, and students are able to produce aromatherapy oils originating from various essential oil variants so that it is hoped that this can help improve relaxation, preventing stress, and increasing income for students. The methode used iss a direct approach, lecture and practicer. The rresults of the sservice activitiess showed an increase in understandingg by comparing the participants' pretest and posttest. This activity ran smoothly and there was high enthusiasm from the participants. Thiss can be seenn ffromm the number of participantss who wanted to try making reed diffuser aromatherapy preparations.